Sexual Orientation and Leadership Suitability: How Being a Gay Man Affects Perceptions of Fit in Gender-Stereotyped Positions - Barrantes, Renzo J.; Eaton, Asia A. (Sex roles, 2018)
The current set of studies examines perceptions of gay men’s fitness for leadership positions in the workplace. In two between-subjects experiments we examined the effect of a male employee’s sexuality on perceptions of his suitability for stereotypically feminine, masculine, and gender-neutral managerial positions, as well as potential mediators (perceptions of target agency and communion) and moderators (target out status) of these effects. In Study 1, 341 U.S. college student participants rated a gay male target as more communal and more suitable for feminine managerial positions than an otherwise identical heterosexual target, irrespective of his “out” status. Moreover, ratings of communion mediated the relationship between targets’ sexuality and suitability for feminine leadership. No differences between gay and heterosexual targets in targets’ agency or targets’ suitability for masculine or gender-neutral managerial positions were detected. Study 2 used a sample of 439 U.S. adults and an ambiguous target’s résumé to replicate and expand Study 1. This study provided participants with conflicting information on targets’ agency and communion, and it assessed the same dependent variables of targets’ agency, communion, and leadership suitability for various positions. Study 2 again found that ratings of communion significantly mediated the relationship between male targets’ sexuality and perceived suitability for feminine managerial roles. These findings extend previous research on perceptions of gay men in the workplace and have practical implications for being “out” at work.